Serum concentration and immunostaining of vascular endothelial growth factor in dogs with multicentric lymphoma - Rodigheri, Sabrina Marin [UNESP]; Calazans, Sabryna Gouveia; Amorim, Reneé Laufer [UNESP]; De Nardi, Andrigo Barboza [UNESP]; Sequeira, Júlio Lopes [UNESP]; Daleck, Carlos Roberto [UNESP] (Universidade Estadual de Londrina, 2015)
Vascular endothelium growth factor (VEGF) is one of the most specific regulators of tumor angiogenesis and lymphangiogenesis. Moreover, VEGF plays a role in tumorigenesis through activation of an autocrine signaling pathway that enables cancer cells to stimulate their own growth. The aim of this study was to investigate VEGF serum levels and immunoexpression in canine multicentric lymphomas and correlate these parameters with the prognostic factors of this cancer. Sixteen dogs were evaluated (eight clinically healthy and eight diagnosed with multicentric lymphoma). The animals underwent blood sampling to measure VEGF serum concentrations and lymph node biopsy to evaluate VEGF immunoexpression. The VEGF immunoreactivity score was higher (p=0.0003) in the lymph nodes of dogs with multicentric lymphoma (8.50±2.33) than in those of healthy dogs (1.87±1.80). There was no significant difference in the VEGF serum concentrations between healthy dogs and dogs with lymphoma (p=0.08). Immunophenotype, clinical stage and grade of malignancy influenced the life expectancy of dogs with lymphoma. Our results showed that VEGF is expressed in high amounts in the lymph nodes of dogs with multicentric lymphoma and may be responsible for the growth, survival and migration of tumor cells.
Keywords: Angiogenesis; Lymphangiogenesis; Oncology; Tumorigenesis; VEGF